MUHAMMADIYAH URBAN: AKSELERASI GERAKAN MUHAMMADIYAH GRESIK KOTA BARU - Fradana, Ahmad Nurefendi (IAIN Palangka Raya, 2020)
This paper reveals the phenomenon that occurred in Muhammadiyah Gresik Kota Baru which, where there is a close relationship between Muhammadiyah and the middle class as the backbone of its movement. It is suspected that an accelerating move occurred in a relatively short time, Muhammadiyah Gresik Kota Baru increased rapid progress. One of the dynamics of Indonesian society that is considered important to be observed is the existence of a slow but sure shift to the sociological conditions and the religiosity of the community. Then created a group of people who came to be called the middle class. This middle class is knowledgeable, highly educated, well-established and open-minded. The next stage, they are determined as: Urban society. Since its inception, Muhammadiyah as a religiously based community organization has ties for the whole community. Muhammadiyah always undertakes multi-step revitalization of its dakwah. These efforts have so far been carried out regularly and regularly and touches almost all layers of society as objects (and subjects) of their missionary movements. This group of people is no exception: Urban society.